DAMPAK PENERAPAN KUOTA IMPOR TERHADAP PERMINTAAN KARET ALAM INDONESIA OLEH NEGARA CHINA - Syaffendi, Muhamad Ridho; Rifin, Amzul; Jahroh, Siti (Jurnal Agribisnis Indonesia, 2013)
Indonesia is once country with an open economy, trade is one way to get the source of income for the country. therefore, Indonesian trying to be a exporters some excellent products, especially in the area of âârubber plantations. This study aims to look and identify the impact of the adoption quota production of natural rubber to Indonesia and other major rubber producing countries in the ASEAN region, in this study using a rubber commodity time series data to be analyzed quantitatively through descriptive models and quantitative models. Deskritptif model used is multiple linear regression model. the results of this study demand for natural rubber imports from ASEAN countries China is influenced by several variables that the price of natural rubber, synthetic rubber prices , income per capita , exchange rates , and dummy variables. Judging from the competitiveness of Indonesias natural rubber can not compete in terms of price with natural rubber Thai state, due to Indonesias natural rubber are substitutes for natural rubber Thailand, while for Malaysia, Indonesias natural rubber relationship is complementary.